IMPLEMENTASI ALGORITMA NAIVE BAYES UNTUK MEMPREDIKSI HASIL PANEN PADI - Abdul Basit (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Rice (Oryza Sativa) is one of the important plants in Indonesia. Rice is produced from rice plants, which is a staple food for the people of Indonesia. One of them is rice producer, Pelabuhan Ratu Distric, the result harvest in Pelabuhan ratu every year experiencing ups and downs that are not stable. As an effort to prevent extreme price increases the need for accurate and accurate predictions about the result harvest in Kecamatan Pelabuhan ratu. lack of predictive advice the result rice harvest resulting in lack of information needed to increase rice production in Kecamatan Pelabuhan ratu. Data mining is one of implementation which is applied to find a model and patterns that are able to make predictions on a data based on previous data in a certain period of time. One algorithm used in data mining techniques for classification is naive bayes. Naive Bayes algorithm is Prediction techniques based on simple possibilities on applying Bayes rules with strong independence. Keywords: Prediction, Harvest Result, Naive Bayes